Adsorption-desorption reactions of selenium (VI) in tropical cultivated and uncultivated soils under Cerrado biome. (December 2016) - Lessa, J.H.L.; Araujo, A.M.; Silva, G.N.T.; Guilherme, L.R.G.; Lopes, G.
Abstract: Soil management may affect selenium (Se) adsorption capacity. This study investigated adsorption and desorption of Se (VI) in selected Brazilian soils from the Cerrado biome, an area of ever increasing importance for agriculture expansion in Brazil. Soil samples were collected from cultivated and uncultivated soils, comprising clayed and sandy soils. Following chemical and mineralogical characterization, soil samples were subjected to Se adsorption and desorption tests. Adsorption was evaluated after a 72-h reaction with increasing concentrations of Se (0–2000 μg L −1 ) added as Na2 SeO4 in a NaCl electrolyte solution (pH 5.5; ionic strength 15 mmol L −1 ). Desorption, as well as distribution coefficients (Kd ) for selenate were also assessed. Soil management affected Se adsorption capacity, i.e., Se adsorbed amounts were higher for uncultivated soils, when compared to cultivated ones. Such results were also supported by data of Kd and maximum adsorption capacity of Se. This fact was attributed mainly to the presence of greater amounts of competing anions, especially phosphate, in cultivated soils, due to fertilizer application. Phosphate may compete with selenate for adsorption sites, decreasing Se retention. For the same group of soils (cultivated and uncultivated), Se adsorption was greater in the clayed soils compared to sandy ones. Our results support the idea that adding Se (VI) to the soil is a good strategy to increase Se levels in food crops (agronomic biofortification), especially when crops are grown in soils that have been cultivated over the time due to their low Se adsorption capacity (high Se availability). Highlights: Soil management affected selenate adsorption capacity of the studied tropical soils. Uncultivated soils adsorbed higher amounts of Se compared to cultivated soils. Selenate is more mobile in cultivated soils than in the uncultivated ones. Higher Kd values were found for uncultivated soils, when compared to cultivated ones.